Synergistic Larvicidal and Pupicidal Effects of Monoterpene Mixtures Against Aedes aegypti with Low Toxicity to Guppies and Honeybees - Sirawut Sittichok; Hataichanok Passara; Tanapoom Moungthipmalai; Jirisuda Sinthusiri; Kouhei Murata; Mayura Soonwera (Insects)
The present study evaluated the larvicidal and pupicidal activities of pure and mixed monoterpene formulations—eucalyptol, geranial, trans-anethole, and trans-cinnamaldehyde—against Aedes aegypti and compared them with 1% (w/w) temephos. Safety bioassays of all formulations on non-target species confirmed their safety. The combined mixture of eucalyptol + trans-anethole at 400 µg/mL exhibited stronger larvicidal activity, with an LC50 of 176 µg/mL, while the combination of trans-anethole + geranial at 400 µg/mL exhibited stronger pupicidal activity with an LC50 of 167 µg/mL. Both formulations were more effective than a 1% temephos. All the mixture formulations were more strongly synergistic compared to pure formulations, with an increased mortality value (IMV) of 25% to 95%. External morphological aberrations observed at death included swelling of the respiratory system. Importantly, all the formulations were safe for two non-target species: guppies (Poecilia reticulata) and honeybees (Apis mellifera). The combination formulations are strong larvicides and pupicides for controlling Ae. Aegypti, which will help reduce the spread of viruses carried by this vector.